EVALUASI PRODUKTIVITAS DAN EFISIENSI ALAT BERAT PADA PEKERJAAN TANAH PROYEK PERPANJANGAN RUNWAY DI BANDARA INTERNASIONAL LOMBOK - AMRUN ZAOQI; HASYIM HASYIM; I GEDE PUTU WARKA (Universitas Mahasaraswati K. Mataram, 2022)
Projects for the extension of the runway and other supporting facilities at the international airport of Lombok, Central Lombok, West Nusa Tenggara (NTB), where the implementation of the work is dominated by the use of heavy equipment to accelerate the completion of the work.The data obtained is by direct observation in the field. Analysis of the calculation of heavy equipment productivity, heavy equipment operating costs, revenue and profit were analyzed using the Bina Marga method. The heavy equipment studied in the field are excavators, dump trucks, motor graders, vibrator rollers, and water tankers.Productivity and the number of tools needed from the analysis results with those in the contract documents are appropriate, while the duration or time of work from the analysis results is more efficient. The hourly rental fee obtained from the calculation results for each heavy equipment, namely Excavator, is Rp. 694,260. Dump trucks of Rp. 753,762. Motor grader Rp. 642.188. Vibratorroller Rp. 551583.4. As for the Watertanker Rp. 384,646.04. The income and profit obtained from the use of heavy equipment on the ground work of the runway extension project at the Lombok international airport with a total of Rp. 38,279,148,142.96 and a profit of Rp. 3,469,922,558.05.